Neighborhood contexts and child maltreatment reports among families receiving AFDC/TANF: a longitudinal and multilevel study - Kim, Hyunil (Child maltreatment, 2022)
Attention to the relationship between neighborhood context and child maltreatment is growing. However, no study exists that considers families’ residential moves and neighborhood changes longitudinally. This is particularly relevant to disadvantaged families who move frequently. Our sample includes children who experienced a child maltreatment report (CMR) or an AFDC case in early childhood. We followed up these children from 1995 to 2009 through various administrative databases. We used multilevel logistic growth curve models to estimate the CMR likelihood at each age from 1 to 16. Estimates were limited to ages on AFDC/TANF to trace families’ residential addresses based on AFDC/TANF payee records. Our findings highlight the importance of tracing residential neighborhoods in a longitudinal study. While doing so, we identify some possible neighborhood contextual influences. These, however, are small in contribution to overall risk and are less observable among children that are more vulnerable.